Corporate governance and information asymmetry - Hamid Salehi; Hamideh Rezaie; Farideh Ansari (Management Science Letters)
The purpose of this study is to investigate the impact of some corporate governance mechanisms on information asymmetry. From among different mechanisms of corporate governance, the number of board members who were not responsible, ownership concentration and the percentage of institutional ownership are considered. Time scale of the study includes the years from 2005 to 2011. Sampling was performed among all the companies accepted in Tehran Stock Exchange using systematic removal method. This sample includes 504 companies-years. This is a post-event study. Experimentally, this study lies in accounting proving research areas and it is based on financial statements of the firms, and regarding purpose is application. Descriptive method has been used in this study. The findings show that there was a positive and significant relationship between the number of board members who are not responsible and the percentage of institutional ownership from the one side, and information asymmetry from the other. In addition, the findings show a negative significant relationship between ownership concentration and information asymmetry.